Likwidacja bractw religijnych w Lublinie w 2. połowie XIX wieku - Partyka, Wiesław (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The brotherhood movement was born in the Church in the 4th century. Brotherhoods were attached to churches and monasteries, and their aim was to strengthen the devotion among the faithful through the implementation of the devotional objectives as well as social and charitable activities. In Poland religious brotherhoods emerged in the 13th century and evolved over the centuries. They flourished in the 17th and 18th centuries in most parishes. In the region of Lublin they appeared in the late 14th century. In Lublin in the 19th century, there were 14 religious brotherhoods. They included a great number of the city residents, taking care of strengthening their piety and morality. Patriotism and religiousness nurtured by the members of religious associations were often not approved of by the authorities of the partitioners, which often resorted to different kinds of repression, including the liquidation of many brotherhoods. In the years 1875-1876, as a result of the Government's order, two brotherhoods were liquidated: the Brotherhoods of the Heart of Jesus and the Holy Name of Mary, and also the association of the penitents attached to the Brotherhood of the Rosary. Despite this repression, the citizens of Lublin were strongly connected with the brotherhood movement, effectively opposing secularism and taking care of their identity as well as values such as love of God and their own country.